Severe macroglossia after posterior fossa and craniofacial surgery in children. Issue 4 (April 2018) - Bouaoud, J.; Joly, A.; Picard, A.; Thierry, B.; Arnaud, E.; James, S.; Hennessy, I.; McGarvey, B.; Cairet, P.; Vecchione, A.; Vergnaud, E.; Duracher, C.; et al.
Abstract: Massive swelling of the tongue can occur after posterior fossa and craniofacial surgery. Several hypotheses have been proposed to explain the occurrence of such severe postoperative macroglossia, but this phenomenon is still poorly understood. Severe postoperative macroglossia can be a life-threatening condition due to upper airway obstruction. Three cases of severe postoperative macroglossia that occurred after cervical spine, craniofacial, and posterior fossa surgical procedures are reported here. These cases required specialized maxillofacial management and a prolonged stay in the intensive care unit. Causal factors involved in this condition are reported, in order to highlight appropriate prevention and treatment options adapted to the management of paediatric patients. An overview of the current literature on severe postoperative macroglossia in paediatric populations is also provided.